The Professional Competence of a University Teacher within the Humanistic Paradigm - Čehlovs, Mihails (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In view of the changes that have taken place in the methodological framework of pedagogy, it is necessary to bring to the foreground issues concerning the professional competence of a university teacher in accordance with the new ideas of the humanistic paradigm. The object of the research – the professional competence of a university teacher. The purpose of the study – to determine the basis, content and structure for the professional competence of a university teacher in new historical circumstances. Research methodology – an aggregate of methods: epistemological (personal activity), culturological, humanistic, and competence-based methods.